Strategic Innovative Management and Sustainable Development of Industrial Enterprises - Dimitrova, Teodora; Komandrovska, Veronika; Marinov, Marin; Taranenko, Artem (Dr. Viktor Koval, 2025)
Introduction. Amidst the dynamic changes in the competitive environment, strategic management of innovative development is a decisive factor in ensuring the stability and sustainable development of industrial enterprises. Despite the importance of innovative development, many enterprises face problems implementing an effective innovation strategy and lacking an innovative culture due to successfully managing projects with a high share of research and development (R&D). Aim and tasks. This study aims to analyse the factors that influence the effectiveness of strategic management in the innovative development of industrial enterprises and to form a case for modelling business processes by assessing the cost component of R&D and its components. Results. The results of the study show that sustainable development of an industrial enterprise is possible under conditions of high-quality strategic management (“Technology Roadmapping” of industrial innovations and the “Open Innovation” model). The effectiveness of strategic management in the development of an industrial enterprise depends on factors such as the development of an innovation culture, investments in innovation processes, the ability of the enterprise to adapt, and the availability of information necessary for making strategic decisions. According to the results obtained in Ukraine, there is an increase in the volume of spending on scientific experiments and developments by 2.1% in 2022 compared to 2018, while spending on applied research increased by 35.3%, with a decrease in spending on scientific experimental developments by 13.1%. According to the results of calculating the correlation coefficient, it was found that there is a close relationship (0.913) between the cost of implementing innovations in production and the cost of R&D, which is the basis for coordinating the modelling of scientific and technical activities and business processes at the regional economy level. Conclusions. During this research, the features of creating a technological map of innovation at an industrial enterprise were considered, and the open innovation model was adapted to the operating conditions of an industrial enterprise. Considering that the innovative basis of industrial content is formed in different regions of Ukraine with different dynamics, a recommendation was made regarding using interregional cooperation tools to form economic models for the sustainable development of industrial enterprises.